Pendampingan Guru dalam Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif pada Pengelolaan Kelas dalam Jaringan - Kabatiah, Maryatun; Siagian, Liber; Wahyudi , Arief; Batubara, Abdinur; Rachman, Fazli (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
Community service activities carried out by a team from the faculty of social sciences at Universitas Negeri Medan took place at State Vocational High School 2 Tebing Tinggi. Implementation of the Community Partnership Program (hereinafter referred to as PKM) which will be carried out to support efforts to implement creative and fun learning and assist in the "Development of Interactive multimedia-based Learning Media in Online Classroom Management". This is one way to increase the competence of teachers of SMKN 2 Tebing Tinggi in online learning using Powtoon Interactive multimedia-based Learning Media. The targets that have been achieved in this PKM are: 1) Powtoon Interactive multimedia-based Learning Media Products. on online class management at State Vocational High School 2 Tebing Tinggi; 2) The use of Powtoon interactive multimedia-based learning media development in online classroom management at State Vocational High School 2 Tebing Tinggi; 3) Improving the competence of teachers of State Vocational High School 2 Tebing Tinggi in online learning using Powtoon Interactive multimedia-based Learning Media.